Desarrollo de una tecnología escala de banco para el secado de crudo de almidón nativo de quinua (2016)
This project focuses on the stage of drying and consist in the development of an appropiate technology for the reduction of moisture in the raw mix, getting quinoa native starch. In the investigation it was found that to achieve the design of the aquipment, both properties of the product to dry (raw quinoa starch) and of the dry product (quinoa native starch) must be meet, which were not available at the time of the development of the project since the characterization will take place in a later project.